1997
DOI: 10.1111/j.1600-0846.1997.tb00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Can early malignant melanoma be differentiated from atypical melanocytic nevi by in vivo techniques?

Abstract: In this study dermoscopy, when used by experienced dermatologists, increased diagnostic sensitivity and index of suspicion but decreased specificity and diagnostic accuracy for diagnosing MM. Therefore, dermoscopy may result in an increased number of biopsies of benign lesions (AMN), but would decrease the probability of missing MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…Those include the principal component transform (PCT)/median cut algorithm [9], adaptive thresholding, the first image plane of the PCT [10], thresholding in the blue image plane [11], k-means clustering [12], split-and-merge [9,13], a segmentation technique based on a Markov random field (MRF) image model [14], and a non-linear diffusion technique [12].…”
Section: Introductionmentioning
confidence: 99%
“…Those include the principal component transform (PCT)/median cut algorithm [9], adaptive thresholding, the first image plane of the PCT [10], thresholding in the blue image plane [11], k-means clustering [12], split-and-merge [9,13], a segmentation technique based on a Markov random field (MRF) image model [14], and a non-linear diffusion technique [12].…”
Section: Introductionmentioning
confidence: 99%
“…5 In recent years, the use of dermoscopy (epiluminescence microscopy, surface microscopy) has been demonstrated to improve the diagnostic accuracy of nearly all pigmented skin lesions. [7][8][9][10][11] Nevertheless, little is known about the possible role of dermoscopy in the diagnosis of mucosal melanosis. 12 A previous study found that a diffuse pigmentation, without any other dermoscopic features related to melanocytic proliferation (''structureless pattern''), was the hallmark of melanosis.…”
mentioning
confidence: 98%
“…The well-done study by Steiner et al 6 was eliminated because of the unavailability of data to calculate dichotomous outcomes of melanoma or nonmelanoma for dermoscopy, although such data were given for the clinical evaluations. Two studies 17,30 were excluded because dermoscopy was compared with pictures taken without oil at magnifications of ϫ16 and ϫ10, respectively, and not with naked-eye examination. The study by Pazzini et al 31 was rejected because the data needed to calculate sensitivity, specificity, and likelihood ratios were not reported, although figures were given for diagnostic accuracy and index of suspicion.…”
Section: Construction Of Sroc Curvesmentioning
confidence: 99%